2022
DOI: 10.1101/2022.08.09.22278128
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variant-risk-exon interplay impacts circadian rhythm and dopamine signaling pathway in severe psychiatric disorders

Abstract: In psychiatric disorders, common and rare genetic variants cause widespread dysfunction of cells and their interactions, especially in the prefrontal cortex, giving rise to psychiatric symptoms. To better understand these processes, we traced the effects of common and rare genetics, and cumulative disease risk scores, to their molecular footprints in human cortical single-cell types. We demonstrated that examining gene expression at single-exon resolution is crucial for understanding the cortical dysregulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 153 publications
0
3
0
Order By: Relevance
“…Although previous research has identified numerous genes associated with disorders such as schizophrenia, the direction of effects and overlap with GWAS findings often vary, indicating a complex relationship between gene expression changes and genetic susceptibility 16,17 . Transcriptome-wide association studies (TWAS), expression quantitative trait loci (eQTL) and eQTScore (association analyses between PRS and gene expression) analyses have further bridged the gap between GWAS findings and gene expression data 9,16,18,19 . These integrative approaches provide insights into how the identified GWAS variants can influence gene expression, thereby contributing to the pathophysiology and a more nuanced understanding of psychiatric disorders 20 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although previous research has identified numerous genes associated with disorders such as schizophrenia, the direction of effects and overlap with GWAS findings often vary, indicating a complex relationship between gene expression changes and genetic susceptibility 16,17 . Transcriptome-wide association studies (TWAS), expression quantitative trait loci (eQTL) and eQTScore (association analyses between PRS and gene expression) analyses have further bridged the gap between GWAS findings and gene expression data 9,16,18,19 . These integrative approaches provide insights into how the identified GWAS variants can influence gene expression, thereby contributing to the pathophysiology and a more nuanced understanding of psychiatric disorders 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Genetic correlation analyses have unveiled distinct interconnected clusters among these disorders, indicating their interconnected nature and underscoring the genetic overlap between mood and psychotic disorders 5 . This shared genetic architecture has been the focus of extensive research [6][7][8][9][10] . Genome-wide association studies (GWAS) have significantly advanced our understanding of the genetic architecture of psychiatric disorders, uncovering numerous significant genetic variants 5,[11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation